Newspapers - Grundy, Peter (Oxford : New York : Oxford University Press, 1993)
This very popular series gives teachers practical advice and guidance, together with resource ideas and materials for the classroom.
Includes bibliography.
Keywords: Newspapers in education; English language -- Usage